God, Happiness and Evil - Khatchadourian, Haig (Religious studies, 1966)
In a recent article, George Schlesinger adds his thoughts to the quite extensive literature on the Problem of Evil and the Problem of Suffering. What is noteworthy about this article is the fact that the author, after briefly discussing a number of familiar arguments for and against the traditional theistic conception of God as both omnipotent and perfectly good, attempts to dissolve the problem itself as a pseudo-problem. In the present paper I wish (1) to try to show that Schlesinger's attempt fails, whether or not he is right in his conclusion that the problem of evil is not a genuine problem; and (2) to raise, in the course of my criticism, certain fundamental questions that must be answered if the controversy between theists and their critics is to become logically capable of resolution. Further, in relation to (1) and (2), I shall (3) offer a very preliminary sketch of some of the fundamental terms or concepts involved in the discussion of the problem of evil and related issues of philosophical theology. I shall begin by saying a few things about Schlesinger's discussion of some of the familiar attempts of theists to resolve the problem, and the equally familiar attacks of the sceptics. I shall then pass to a criticism of Schlesinger's main thesis.